Behavioral activation therapy for depression is associated with a reduction in the concentration of circulating quinolinic acid. Issue 13 (25th October 2022) - Savitz, Jonathan; Ford, Bart N.; Yeh, Hung-Wen; Akeman, Elisabeth; Cosgrove, Kelly; Clausen, Ashley N.; Martell, Christopher; Kirlic, Namik; Santiago, Jessica; Teague, T. Kent; Irwin, Michael R.; Paulus, Martin P.; et al.
Abstract: Background: An inflammation-induced imbalance in the kynurenine pathway (KP) has been reported in major depressive disorder but the utility of these metabolites as predictive or therapeutic biomarkers of behavioral activation (BA) therapy is unknown. Methods: Serum samples were provided by 56 depressed individuals before BA therapy and 29 of these individuals also provided samples after 10 weeks of therapy to measure cytokines and KP metabolites. The PROMIS Depression Scale (PROMIS-D) and the Sheehan Disability Scale were administered weekly and the Beck depression inventory was administered pre- and post-therapy. Data were analyzed with linear mixed-effect, general linear, and logistic regression models. The primary outcome for the biomarker analyses was the ratio of kynurenic acid to quinolinic acid (KynA/QA). Results: BA decreased depression and disability scores ( p 's < 0.001, Cohen's d 's > 0.5). KynA/QA significantly increased at post-therapy relative to baseline ( p < 0.001, d = 2.2), an effect driven by a decrease in QA post-therapy ( p < 0.001, uncorrected, d = 3.39). A trend towards a decrease in the ratio of kynurenine to tryptophan (KYN/TRP) was also observed ( p = 0.054, uncorrected, d = 0.78). Neither the change in KynA/QA, nor baseline KynA/QA were associated with response to BA therapy. Conclusion: The current findings together with previous research show that electronconvulsive therapy, escitalopram, and ketamine decrease concentrations of the neurotoxin, QA, raise the possibility that a common therapeutic mechanism underlies diverse forms of anti-depressant treatment but future controlled studies are needed to test this hypothesis.